Introdução da álgebra: desenvolvimento do pensamento algébrico no 6° ano do ensino fundamental - Dias, Lindinalva da Silva (Universidade Federal de São Carlos, 2019)
The present research presents a study about algebraic thoughts expressed by students of the 6th grade of elementary school. The research’s objective was to investigate the implications of a teaching sequence, based on problem solving, in the introduction of the initial thoughts of algebra with 6th grade students. This is a qualitative research and it is based on Ponte, Branco and Matos (2009) and Booth (1994). The research was applied to 19 students from the 6th grade of Elementary School of a public school at Sorocaba city, state of São Paulo. The students were divided in pairs and underwent a teaching intervention consisting of 6 meetings of 50 minutes each, in which 6 activity sheets were distributed. The students were divided in pairs to work with the activities. From the activities developed by the students it was possible to analyze and verify they better understood the concepts involved in the practical and pictorial parts, it means, activities involving figures to represent the context of the statement, besides the manipulation of the two-plate scale, and manipulative objects such as EVA. It is also important to note that the algebraic activities (equations), in which the values of the unknowns were given to the students, did not show any difficulty, but an activity in which they had to "find out" the value of the unknown was difficult to understand the equivalence between the two members of the equation. The relevance of this research is due to the fact that it is important to work with the students at the beginning of their study with algebra starts, mainly with playful and practical activities. As students begin to have contact with algebra from the 7th grade of Elementary School.
Introduction of algebra: development of algerian thought in the 6th grade of elementary school
Keywords: Álgebra, Ensino Fundamental, situações problema, ensino e aprendizagem.; Algebra, Elementary education, problem situations, teaching and learning; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ALGEBRA::CONJUNTOS